Synergetic effect of Y2O3 rare-earth oxide and in-situ phases on corrosion and wear properties of AlSi10Mg aluminium matrix composites produced by hot pressing - Cingoz, Umut Can; Kisasoz, Burcin Ozbay; Bayrak, Yahya; Kisasoz, Alptekin (ELSEVIER SCI LTD, 2025)
In this study, the influence of Y2O3 addition on the properties of AlSi10Mg alloy was investigated. It was also aimed to improve tribological and corrosion behaviour of the aluminium matrix via the existence of Y2O3 particles and in-situ formed phases. For this purpose, the AlSi10Mg matrix Y2O3 reinforced composites were fabricated by hot pressing. The composites were produced at 500 degrees C with 1, 3, 5, and 10 wt% Y2O3 ratios under 200 MPa. The microstructure analyses revealed that in-situ phases like MgAl2O4, Y3Al5O12 and MgY were comprised in 5 and 10 wt% Y2O3 containing samples. Moreover, increasing Y2O3 content caused an increase in the porosity content of the produced samples. However, the wear behaviour of the samples was improved with Y2O3 addition and in-situ formed phases. The wear rate of AlSi10Mg was found as 1.73.10-3 mm3/Nm, and it was reduced to 0.93.10-3 mm3/Nm in 10 wt% Y2O3 containing sample. On the other hand, both potentiodynamic polarization and immersion corrosion tests showed that the 10 wt% Y2O3 containing sample possessed the worst corrosion behaviour owing to combined effect of the in-situ formed intermetallic, higher Y2O3 ratio and porosity content of the sample. It was observed that 5 wt% Y2O3 containing sample provided the optimum combination of microstructure properties, corrosion resistance and wear behaviour. In conclusion, it was determined that the in-situ phases improved the properties of the AlSi10Mg alloy; in particular, the formation of the Y3Al5O12 phase enhanced the corrosion behavior, while the formation of the MgY intermetallic phase enhanced the wear resistance.
Keywords: Hot pressing (A); Composites (B); Corrosion (C); MECHANICAL-PROPERTIES; METAL-MATRIX; BEHAVIOR; MICROSTRUCTURE; ALLOY; HARDNESS; FATIGUE; Materials Science